2020
DOI: 10.1002/cctc.201902286
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Isomorphous Substitution: An Efficient and Alternative Route to Fabricate the Zn Rich Phase Pure (Cu1−x,Znx)2(OH)2CO3 Precursor Catalyst for Methanol Synthesis

Abstract: A new methodology has been demonstrated for the synthesis of a series of phase pure (Cu1−x,Znx)2(OH)2CO3 precursors by isomorphous substitution of Zn2+ in the malachite structure. By following the present protocol, it was possible to synthesize the pure phase (Cu1−x,Znx)2(OH)2CO3 with substitution level as high as x=0.5, which is better than the maximum possible value achieved by coprecipitation method, i. e. x=0.31. The isomorphous substitution by Zn2+ leads to the change in the morphology of malachite crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The synthesis of Zn doped malachite was carried out by isomorphous substitution (IS) method as described in our previous publication. [48] The filtered and washed malachite was mixed with 100 mL deionised water and kept at constant temperature bath (60°C). According to the molar ratio of Zn/Cu = 45 : 100, the 0.05 M solution of Zn(NO 3 ) 2 × 6H 2 O was rapidly added to the slurry using peristaltic pump, and aged for 1.5 h with constant stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of Zn doped malachite was carried out by isomorphous substitution (IS) method as described in our previous publication. [48] The filtered and washed malachite was mixed with 100 mL deionised water and kept at constant temperature bath (60°C). According to the molar ratio of Zn/Cu = 45 : 100, the 0.05 M solution of Zn(NO 3 ) 2 × 6H 2 O was rapidly added to the slurry using peristaltic pump, and aged for 1.5 h with constant stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of zM, (Cu,Zn) 2 (OH) 2 CO 3 . The synthesis of Zn doped malachite was carried out by isomorphous substitution (IS) method as described in our previous publication [48] . The filtered and washed malachite was mixed with 100 mL deionised water and kept at constant temperature bath (60 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was found that when the Cu/ZnO/Al 2 O 3 catalyst was prepared using a co-precipitation method, the precipitates formed mainly included zinc-malachite, aurichalcite and layered double hydroxides. [17][18][19][20][21] Catalysts derived from zinc-malachite often have excellent performance. By adjusting the pH value, Gao W et al prepared Cu-ZnO-ZrO 2 catalysts with aurichalcite and zinc-malachite as precursors, and found that the catalyst derived from zinc-malachite had an excellent catalytic performance for methanol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…25 The existence of single CuO and ZnO is inhibited after the calcination of the precursor, which promotes the formation of Cu-ZnO interfaces. 21 Hence, the use of zinc-malachite as the precursor to construct Cu/ZnO/Al 2 O 3 catalysts with rich Cu-ZnO interfaces is promising. As far as we know, the current research mainly focuses on the Cu/ ZnO/Al 2 O 3 catalysts prepared by adjusting the zinc substitution amount of zinc-malachite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation